National Association of Social Workers oral history interviews - National Association of Social Workers; Bartlett, Harriett M. (Harriett Moulton); Dunham, Arthur, 1893-; Grayson, Vida S.; Johnson, Arlien; Konopka, Gisela; Lindsay, Inabel B., 1900-; Perlman, Helen Harris; Ryland, Gladys; Wilson, Gertrude
Transcripts of oral history interviews conducted by Vida S. Grayson with educators and practicioners from various branches of social work, geographical regions, and ethnic backgrounds documenting the development of the field from the 1920s through the 1970s. Interviewees include Harriett M. Bartlett, Arthur Dunham, Arlien Johnson, Gisela Konopka. Inabel B. Lindsay, Helen Harris Perlman, Gladys Ryland, and Gertrude Wilson.
Professional organization established in 1955.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Social service; Social workers -- Interviews